COMPARING TECHNIQUES FOR ABDOMINAL RECTOPEXY IN RECTAL PROLAPSE: A RANDOMIZED CONTROLLED STUDY. - Jai Prakash Sinha,; Kunal, (Student's Journal of Health Research Africa, 2024)
Background Abdominal rectopexy is a surgical option for rectal prolapse, but various techniques exist, prompting the need for comparative studies to assess their efficacy and safety. The study aimed to compare different techniques of abdominal rectopexy for rectal prolapse treatment, evaluating their effectiveness, safety, and long-term outcomes. Methods A randomized controlled trial design was employed. Forty participants meeting inclusion criteria (full-thickness rectal prolapse, ability to participate, informed consent) were included. Exclusion criteria encompassed irreducible prolapse, age below 18, and pregnancy. Randomization, stratification, and blinding techniques were used to minimize bias. Primary outcomes included bowel function, quality of life (QoL), recurrence rates, and surgical complications, assessed using validated measures and statistical analyses. Results Forty participants were randomized into perineal (n=20) or abdominal (n=20) groups. Both groups showed significant improvement in bowel function postoperatively (p < 0.001), with increased bowel movements, faster evacuation, and reduced incomplete evacuation. QoL scores significantly improved across all dimensions (p < 0.001). Recurrence rates were 10% in the perineal group at 1 year and increased to 15% at 3 years. Minor complications occurred in 20% of perineal and 15% of abdominal cases within 30 days, with no major complications. Conclusion Abdominal rectopexy techniques demonstrate improved bowel function and QoL, but long-term recurrence rates require monitoring. Both perineal and abdominal approaches show safety and efficacy, with considerations for recurrence and minor complications. Recommendations Continued follow-up and larger studies are recommended to validate findings and guide clinical practice.